Housing, food and dignity: the food worlds of homeless families in emergency accommodation in Ireland. Issue 2 (2nd July 2020) - Share, Michelle
ABSTRACT: Family homeless is an increasing challenge across the western world and no longer confined to marginalized groups. In Ireland, it extends to those who have become homeless because of an economic housing crisis, which has resulted in an unprecedented number of families living in emergency accommodation such as B&Bs and hotels. Homelessness impacts on all aspects of everyday life, not least food and eating. Using the photo-elicitation technique, the study examined how families living in emergency accommodation accessed, stored, cooked, and consumed food, the strategies they used to manage the impact of their food and eating situation, and how the overall situation in regard to food and eating made them feel. Food storage was a constant everyday pressure that impacted on food choice and dignity and constrained choices to the extent that families relied on takeaway meals and convenience foods. Regimented meal times and restricted kitchen access greatly challenged parents' food provision efforts and negatively influenced children's and parents' dietary intake. The importance of space and the micro-contexts where food is procured, prepared, eaten and disposed is highlighted as is the need for homeless service design that supports positive family food practices and dignity.